GaAs quantum well‐dots solar cells with spectral response extended to 1100 nm. Issue 20 (1st October 2015) - Mintairov, S.A.; Kalyuzhnyy, N.A.; Maximov, M.V.; Nadtochiy, A.M.; Rouvimov, S.; Zhukov, A.E.
Abstract : Expanding the photosensitivity spectrum of a single‐junction GaAs‐based solar cell to 1100 nm by using InGaAs hybrid quantum well dots (QWDs) multilayer media is reported. This nanostructure represents an In0.3 Ga0.7 As quantum wells with modulation of thickness and composition. Up to 15 QWD layers alternated with GaAs spacers can be inserted in an i‐region of the GaAs p–i–n junction without impairing its crystal quality and quantum efficiency in spectral interval of GaAs absorption. The QWD layers are responsible for appearance of a longer wave spectral response (900–1100 nm). A photocurrent increment as high as 4.6 (5.2) mA/cm 2 for terrestrial (space) spectrum is demonstrated.